Evaluation of the Efficacy and Safety of Low Power Diode Laser Therapy for the Treatment of Chronic Gingivitis in Skopje Hospital Macedonia - Spiroski, Milla; Igor Belenichev (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Chronic gingivitis is the most common inflammatory periodontal disease, affecting up to 50% of adults. Low-power diode laser therapy (LLLT) has been proposed as an alternative treatment for chronic gingivitis. Methods: A double-blind randomized controlled study was conducted to evaluate the effectiveness and safety of LLLT in the treatment of chronic gingivitis. Thirty patients with chronic gingivitis were randomly divided into two groups: the control group (n=15) and LLLT group (n=15). The LLLT group received LLLT therapy for 10 minutes per session, twice daily for 14 days. Plaque index (PI), gingival bleeding index (GI), periodontal pocket depth (PPD), and degree of attachment loss (CAL) were measured before and after treatment. Results: The LLLT group showed significant reductions in PI, GI, PPD, and CAL compared with the control group. The difference between the two groups was statistically significant (p<0.05). No side effects were reported during the study. Conclusion: LLLT has been proven to be effective and safe in the treatment of chronic gingivitis. LLLT may be a useful alternative treatment option for patients with chronic gingivitis.